Effects of the Determinants of Foreign Direct Investment in Nigeria: Error Correction Mechanism - Kolawole, EBIRE; O. Lucky, ONMONYA; V. Ekemini, INIM (Asian Journal of Economics and Empirical Research, 2018)
To attract more Foreign Direct Investment (FDI) inflows is the important institutional policies of the most of nations all over the world. Identifying the key determinants of FDI inflows is therefore seen as an important task for policy makers. This study, therefore, investigates the major determinants of FDI in Nigeria spanning from 1986 - 2017. The secondary source of data was used for the study which was first subjected to stationarity test using Augmented Dickey-Fuller and Phillips Perron test. Findings showed that all variables were found to be integrated order one. Cointegration analysis showed that there exists a long run relationship among the variables. Based on this findings, Error Correction Mechanism was used in testing the hypotheses. The result showed that exchange rate, GDP, first lag of GDP, military expenditure, first lag of military expenditure, political stability and financial development are the major determinants of FDI inflows to Nigeria. The empirical findings of this study show that government at all levels should tackle the menace of insecurity ravaging the economy and portraying the country as insecure thereby creating a secure environment for FDI inflows. Democratic regimes should be sustained and investment policies should be instituted or improved on, in order to create a friendly environment to attract more FDI inflows.